(3GdWHbGJ GdcHQis - (3eMeO Hf SYO Hf efjY GdRgQj, CHh YHO Gddg cGJH GdhGbOj, GHf SYO , J (B230 (3g` s ((3eMeO Hf MSf GdgQbdj s)
(3ChdgG (B:s
(3aj PcQ ef EfJei Edjg QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3aj PcQ GdYbHI GdBNQI s
(3GfXQ GjVG Qbe (B322s
(3Qbe (B1132 (3JGQjNs
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG JbjjOGJ s
(3fSNI QGHYI s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs